Effect of Anaerobic Growth on Quinolone Lethality with Escherichia coli - Malik, Muhammad (American Society for Microbiology, 2007)
Quinolone activity against Escherichia coli was examined during aerobic growth, aerobic treatment with chloramphenicol, and anaerobic growth. Nalidixic acid, norfloxacin, ciprofloxacin, and PD161144 were lethal for cultures growing aerobically, and the bacteriostatic activity of each quinolone was unaffected by anaerobic growth. However, lethal activity was distinct for each quinolone with cells treated aerobically with chloramphenicol or grown anaerobically. Nalidixic acid failed to kill cells under both conditions; norfloxacin killed cells when they were grown anaerobically but not when they were treated with chloramphenicol; ciprofloxacin killed cells under both conditions but required higher concentrations than those required with cells grown aerobically; and PD161144, a C-8-methoxy fluoroquinolone, was equally lethal under all conditions. Following pretreatment with nalidixic acid, a shift to anaerobic conditions or the addition of chloramphenicol rapidly blocked further cell death. Formation of quinolone-gyrase-DNA complexes, observed as a sodium dodecyl sulfate (SDS)-dependent drop in cell lysate viscosity, occurred during aerobic and anaerobic growth and in the presence and in the absence of chloramphenicol. However, lethal chromosome fragmentation, detected as a drop in viscosity in the absence of SDS, occurred with nalidixic acid treatment only under aerobic conditions in the absence of chloramphenicol. With PD161144, chromosome fragmentation was detected when the cells were grown aerobically and anaerobically and in the presence and in the absence of chloramphenicol. Thus, all quinolones tested appear to form reversible bacteriostatic complexes containing broken DNA during aerobic growth, during anaerobic growth, and when protein synthesis is blocked; however, the ability to fragment chromosomes and to rapidly kill cells under these conditions depends on quinolone structure.